Screening attendance of breast or cervical cancers and its associated factors among 30–49 year old women in Gedeo zone, South Ethiopia: Cross-sectional study - Abel Desalegn Demeke; Bedilu Deribe; Martha Girma; Muluken Gizaw; Sefonias Getachew; Susanne Unverzagt; Eva J. Kantelhardt; Betty Ferrell; Eric Sven Kroeber; Lesley Taylor (PLoS ONE, 2025)
Introduction Breast and cervical cancers are the most frequent and fatal cancers among women. Thus, early detection is necessary to improve the prognosis of affected women. However, in Ethiopia, the rates of screening remain alarmingly low. Objective To assess the magnitude of screening attendance for breast or cervical cancer, as well as the factors that predict it, among women aged 30–49 years old in Gedeo Zone, South Ethiopia, in 2023. Method A community-based cross-sectional study was conducted using a multi-stage cluster sampling technique. Data were collected using pretested, structured questionnaires by trained interviewers. Univariate and multivariate logistic regression models were employed to identify factors associated with screening attendance. Results A total of 554 women participated in the study. Of them, 132 (23.8%) were screened for breast or cervical cancer. Higher age of 40–44 versus 45–49 years (adjusted odds ratio [AOR] 4.18 [95% CI 1.59, 10.9]), higher education status ([AOR] 5.49 [95% CI 2.01, 13.1]), having family or a friend with history of breast or cervical cancer ([AOR] 5.55 [95% CI 2.47, 12.5]), short anticipated time to seek help ([AOR] 4.66 [1.31, 11.7]), adequate health literacy ([AOR] 6.98 [95% CI 2.82,13.3]) and high self-efficacy ([AOR] 2.32 [95% CI 1.08, 4.96]) were positive factors with higher screening attendance. High response cost ([AOR] 0.19 95% CI [0.08, 0.50]) was a negative factor and associated with lower screening attendance. Conclusion and recommendation The study found that only one in four women attended breast or cervical cancer screening. Screening uptake was better in women with higher education, health literacy, self-efficacy, and older age–similar to factors associated with other health seeking behavior. Interestingly, history of breast or cervical cancer in a friend or relative was also associated with higher uptake. This indicates that in addition to awareness campaigns, personal testimonials of survivors could encourage women to visit screening facilities.